Risk of rebleeding from gastroesophageal varices after initial treatment with cyanoacrylate; a systematic review and pooled analysis - Zixuan Hu; Decai Zhang; Joel Swai; Tao Liu; Shaojun Liu (BMC Gastroenterology, 2020)
Abstract Background Cyanoacrylate alone or in combination with other interventions, can be used to achieve variable rates of success in preventing rebleeding. Our study aims to assess the pooled risk of gastric and esophageal varices rebleeding after an initial treatment with cyanoacrylate alone and/or in combination with other treatments, by a systematic review of the literature and pooled analysis. Methods PubMed, EMBASE, SCOPUS, and the Cochrane library were searched for studies that reported the risk of rebleeding during the follow-up period after treatment of gastric or esophageal varices with either cyanoacrylate alone or in combination with other treatments. Standard error, upper and lower confidence intervals at 95% confidence interval for the risk were obtained using STATA Version 15 which was also used to generate forest plots for pooled analysis. The random or fixed effect model was applied depending on the heterogeneity (I2). Results A total of 39 studies were found to report treatment of either gastric or esophageal varices with either cyanoacrylate alone or in combination with other treatments. When gastric varices are treated with cyanoacrylate alone, the risk of rebleeding during the follow-up period is 0.15(Confidence Interval: 0.11–0.18). When combined with lipiodol; polidocanol or sclerotherapy the rebleeding risks are 0.13 (CI:0.03–0.22), 0.10(CI:0.02–0.19), and 0.10(CI:0.05–0.18), respectively. When combined with percutaneous transhepatic variceal embolization; percutaneous transhepatic variceal embolization; endoscopic ultrasound guided coils; or with ethanolamine, the rebleeding risk are 0.10(CI:0.03–0.17), 0.10(CI:0.03–0.17), 0.07(CI:0.03–0.11) and 0.08(CI:0.02–0.14), respectively. When esophageal varices are treated with cyanoacrylate alone, the risk of rebleeding is 0.29(CI:0.11–0.47). When combined with percutaneous transhepatic variceal embolization; sclerotherapy; or band ligation, the risks of rebleeding are 0.16(CI:0.10–0.22), 0.12(CI:0.04–0.20) and 0.10(CI:0.04–0.24), respectively. When combined with a transjugular intrahepatic portosystemic shunt; or ethanolamine, the risks of rebleeding are 0.06(CI: − 0.01-0.12) and 0.02 (CI: − 0.02-0.05), respectively. Conclusion In treating both gastric and esophageal varices, cyanoacrylate produces better results in terms of lower risk of rebleeding when combined with other treatments than when used alone. The combination of cyanoacrylate with ethanolamine or with endoscopic ultrasound guided coils produces the lowest risk of rebleeding in esophageal and gastric varices, respectively. We call upon randomized trials to test these hypotheses.